Mathematic Games as an Educational Technology Strategy to Improve Motivation and Learning Outcomes of Elementary School Students - Serni Mulia Hartati; Ulfia Rahmi; Jasrial; Ridwan (Postgraduate, University of Mataram, 2025)
This study investigated the effect of Mathematics Games and learning motivation on the mathematics achievement of fifth-grade students at SDN 03 Koto Kaciak. Using a quantitative approach with a 2×2 factorial quasi-experimental design, students were assigned to experimental and control groups. Data were collected through pre- and post-tests and a learning motivation questionnaire. Two-way ANOVA was used for analysis. The results showed that the Mathematics Games method did not significantly affect learning outcomes (p > 0.05), although the experimental group demonstrated slightly higher mean scores than the control group. In contrast, learning motivation significantly influenced students’ mathematics achievement (p < 0.05), with high-motivation students outperforming their peers. No significant interaction was found between teaching method and motivation level. These findings suggest that while the Mathematics Games method did not produce statistically significant gains, learning motivation remains a key factor in academic success. The study’s contribution lies in its contextual application of Mathematics Games as an instructional strategy in a rural elementary school setting, highlighting the importance of implementation quality and learner characteristics. Further research with longer treatment duration and larger samples is recommended to assess long-term effects and refine the integration of educational games in elementary mathematics instruction.